MODEL PIDANA KERJA SOSIAL SEBAGAI PENGGANTI PIDANA KURUNGAN DALAM RANGKA MENGATASI PERMASALAHAN KELEBIHAN KAPASITAS LEMBAGA PEMASYARAKATAN DI INDONESIA - Yolanda Rizky Rinaldi; Emilda Firdaus; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Almost all prisons and detention centers in Indonesia face the problem of overcapacity which causes prisons unable to carry out their functions optimally. This is because criminalization in Indonesia is more inclined towards imprisonment. The criminal service order is present as an alternative punishment to the crime of deprivation of liberty. The existence of Criminal Service Order is expected to be a solution to the problem of overcapacity in correctional institutions in Indonesia. The purpose of writing a thesis, namely; First, to find out and understand whether the Criminal Service Order’s Model can be used as a Substitute for the Crime of Imprisonment in the Context of Overcoming the Problem of Overcapacity in Prisons in Indonesia.This type of research used in this legal research is normative juridical method, because the purpose of this study is to provide a systematic and comprehensive description or description. In this study the authors conducted research on legal synchronization, by identifying in advance the legal principles that have been proposed in the RUUKUHP. The data source used is secondary data. The data collection technique in this research is the literature review method after the data is collected and then analyzed to draw conclusions.From the results of research and discussion it is known that, first, imprisonment penalties that implement a system of deprivation of liberty do not have a useful purpose of punishment and result in overcapacity in prisons. The emergence of social work punishment as a substitute for imprisonment is deemed to be commensurate with the criminal act committed, namely minor crimes with a short sentence. And a convicted social worker does not need to live in a correctional facility. Second, social work punishment as a substitute for imprisonment would ideally be implemented in Indonesia if in carrying out the sentence there is supervision from the supervisory team and in its implementation there is cooperation with the Social Service and the Environmental Service.Keywords: Criminal Serivice Orders – Criminal Confinement – Over Capacity – Correctional Institution